A review of the aphaenopsian ground beetle genus Uenotrechus Deuve et Tian, 1999 (Coleoptera: Carabidae: Trechinae) - Wei, Guofu; Chen, Jujian; Tian, Mingyi (Zootaxa, 2017)
Uenotrechus Deuve et Tian, 1999, one of the highly cave-adapted genera of the ground beetles, is reviewed. New record of the type species U. liboensis Deuve et Tian, 1999 and descriptions and illustrations of two remarkable new species are provided: Uenotrechus gejianbangi Tian et Wei, sp. n. (type locality: Cave Ji Dong, Neiwen Tun, Huanjiang County, northernmost Guangxi), Uenotrechus deuvei Tian et Chen, sp. n. (type locality: Cave Longmu Dong I, Du’an County, northern Guangxi). U. nandanensis bona sp. is proposed as an independent species. A distribution map and a key to all species of Uenotrechus are also given.